2020
DOI: 10.1002/alr.22702
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory features and predictors for postsurgical outcomes in patients with nasal polyps stratified by local and systemic eosinophilia

Abstract: BackgroundIn this study we aimed to identify inflammatory patterns and predictors associated with clinical outcomes in chronic rhinosinusitis with nasal polyps CRSwNP patients with different blood and tissue eosinophilia Methods A total of CRSwNP patients were enrolled and the expression of biomarkers together with eosinophil and neutrophil counts in nasal polyps were analyzed in a subset of patients Patients were stratified on the basis of blood ≥ × /L and tissue > eosinophilia Logistic regression models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…A total of 1181 Chinese patients with bilateral CRSwNP was initially identified. Then patients with the following items were excluded: (1) Patients were treated with systemic corticosteroids within 3 months or internasal corticosteroids within 1 month before surgery and routine blood test, 17 by cross‐referencing patient's medication history with the electronic prescription record system. (2) Patients with fungal rhinosinusitis, cystic fibrosis, antrochoanal polyps, gastro‐esophageal reflux disease, or sinonasal tumors.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 1181 Chinese patients with bilateral CRSwNP was initially identified. Then patients with the following items were excluded: (1) Patients were treated with systemic corticosteroids within 3 months or internasal corticosteroids within 1 month before surgery and routine blood test, 17 by cross‐referencing patient's medication history with the electronic prescription record system. (2) Patients with fungal rhinosinusitis, cystic fibrosis, antrochoanal polyps, gastro‐esophageal reflux disease, or sinonasal tumors.…”
Section: Methodsmentioning
confidence: 99%
“…190 Limited available data suggest that higher intensity of T1 and T3 inflammation also favors surgical failure. 188,191 It should be highlighted that many of these larger studies examining T2 biomarkers for predicting surgical outcomes have been conducted in Asia, especially China, where CRSwNP is more endotypically heterogeneous. Whether these same biomarkers will prove useful in Western populations where CRSwNP is more homogenously T2 remains an area of active investigation.…”
Section: Surgerymentioning
confidence: 99%
“…Using cluster analysis, Liao et al 8 detected two distinct clusters characterized by T2 response and eosinophil‐dominated endotype, and neutrophil‐dominated endotype with high IL‐8 levels. Consistently, studies in China and Korea have shown that only a small percentage of CRSwNP patients (4.4%–11.2%) exhibited both high eosinophilic and neutrophilic inflammation 39–41 . In contrast, recent studies indicate a positive interaction between eosinophilic and neutrophilic inflammation in CRSwNP patients in Western countries 42 .…”
Section: Distinct Characteristics Of Crs In Asian Patientsmentioning
confidence: 66%
“…Consistently, studies in China and Korea have shown that only a small percentage of CRSwNP patients (4.4%-11.2%) exhibited both high eosinophilic and neutrophilic inflammation. [39][40][41] In contrast, recent studies indicate a positive interaction between eosinophilic and neutrophilic inflammation in CRSwNP patients in Western countries. 42 CRSwNP patients with markedly eosinophilic inflammation exhibit substantial levels of neutrophil infiltration.…”
Section: Eosinophilic and Neutrophilic Inflammationmentioning
confidence: 93%